2012
DOI: 10.1007/s12272-012-0416-0
|View full text |Cite
|
Sign up to set email alerts
|

Induction of apoptosis by ginsenoside Rk1 in SK-MEL-2-human melanoma

Abstract: Ginsenosides are active compounds isolated from Panax ginseng Meyer. Among these ginsenosides, less polar ginsenosides such as ginsenoside Rg3 and ginsenoside Rh2 have been demonstrated to have tumor inhibitory effects because of their cytotoxicity. In this study, we evaluated the apoptotic effects of ginsenoside Rk1 in SK-MEL-2 human melanoma. Ginsenoside Rk1 isolated from red ginseng is one of the novel ginsenosides that shows strong cytotoxicity compared to ginsenoside Rg3 in dose- and time-dependent manner… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
36
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(37 citation statements)
references
References 11 publications
1
36
0
Order By: Relevance
“…In 1979, maltol (3-hydroxy-2-methyl-4-pyrone) (79) was isolated from ginseng (46). In 1981, another three phenolic acids were obtained from the ether-soluble acidic fraction of fresh ginseng, and they were identified by chemical and spectrometric methods to be salicylic acid (80), vanillic acid (81), and p-hydroxycinnamic acid (82) (47).…”
Section: Phenolic Acidmentioning
confidence: 99%
“…In 1979, maltol (3-hydroxy-2-methyl-4-pyrone) (79) was isolated from ginseng (46). In 1981, another three phenolic acids were obtained from the ether-soluble acidic fraction of fresh ginseng, and they were identified by chemical and spectrometric methods to be salicylic acid (80), vanillic acid (81), and p-hydroxycinnamic acid (82) (47).…”
Section: Phenolic Acidmentioning
confidence: 99%
“…Fei et al found that ginsenoside Rh2 induced apoptosis of human melanoma A375-S2 cells in vitro, and that the apoptosis was partially dependent on the caspase-8 and caspase-3 pathway [8]. Kim et al reported that ginsenoside Rk1 induced apoptosis in SK-MEL-2 human melanoma through both extrinsic and intrinsic pathways, including Fas, Fas L, Bax, procaspase-8, procaspase-3, mutant p53, and Bcl-2 [9]. Hasegawa et al found that 20 (S)-protopanaxatriol (M4), the main bacterial metabolite of protopanaxatriol-type ginsenoside, when given prior to i.v.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have reported anti-tumor effects of the components and metabolites of ginseng [5][6][7][8][9][10]. Lee et al found that an acidic polysaccharide ginsan exhibited in vivo anti-tumor activity in a murine B16 tumor model as an immunostimulator of activated T cells, natural killer (NK) cells, and macrophages [5].…”
Section: Introductionmentioning
confidence: 99%
“…Out of the 21 studies included, 16 studies were related to the effectiveness of G-Rk1 only and five studies were reported on the combined effects of G-Rk1 and G-Rg5. The most common study design was in vitro study with 16 studies (Kim et al 2008;Ko et al 2009;Lee et al 2010;Park et al 2002;Lim et al 2009;Jing et al 2006;Kim et al 2012;Bao et al 2005;Ju et al 2012;Liu et al 2007;Park et al 2015;Kim et al 2010;Kang et al 2006;Siddiqi et al 2014;Kang et al 2007), while in vivo study was less common with only two studies (Toh et al 2011;Erb et al 2005). The remaining three articles were both in vitro and in vivo study (Lee.…”
Section: Study Characteristicsmentioning
confidence: 99%
“…Various studies have confirmed the anti-cancer effects of G-Rk1 on different neoplastic cells including hepatocellular carcinoma and melanoma cells (Kim et al 2012;Kim et al 2008). In recent studies, G-Rk1 has been confirmed as a new endothelial barrier enhancer, which is capable of preventing or even reversing the vascular endothelial growth factor (VEGF)-induced vasopermeability in the endothelial cells, thus highly valuable for the pharmaceuticals development, which may effectively control the pathologic vascular leakage (Maeng et al 2013).…”
Section: Introductionmentioning
confidence: 98%